The Currency Composition of Firms' Balance Sheets and its Effect on Asset Value Correlations and Capital Requirements - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2016)
We extend the Tasche (2007) model on the asset correlation bias caused by a currency mismatch between assets and liabilities to the more realistic situation where some assets, and some, but not necessarily all, liabilities, are denominated in a foreign currency. To test the significance of the remaining bias we rely on a unique data base constructed by The Inter-American Development Bank (IADB) containing time-series of the asset- and liability currency composition of firms in a group of Latin American countries. Net currency mismatches are calculated and are found to vary from country to country. The correlation bias itself also varies significantly from country to country and has often been economically significant during the last 20 year-period. We find that the bias regularly is of the same magnitude as the correlation itself even in countries where the average firm has a fairly low degree of currency mismatch. Looking at market-wide corporate credit portfolios in four Latin American countries, we show that the credit risk, and associated Basel II capital charges, could increase by as much as a fifth, on average across our sample, if the actual currency mismatch in firms' balance sheets is acknowledged. In some cases the currency mismatch-induced capital charge could increase much more, sometimes to levels several times (hundreds of percent) the original capital requirement.
Keywords: F31; G10; G15; G21; G33; 330; asset correlation; bias; exchange rate; currency composition; currency mismatch